MAPPING OF VEHICLE EMISSIONS IN ZONGULDAK PROVINCE - Bayik, Gülçin Demirel; Alpan, Mine Polat; Bayik, Caglar; Taniş, Mustafa (MATTER: International Journal of Science and Technology, 2018)
Increase in the rate of individual vehicle use and decrease in the usage habits of public transportation results in significant increase in traffic-related emissions. One of the most important factor among these is the number of vehicles that increases day by day especially in developing countries. In Zonguldak, the number of vehicles have also increased by 21% in the last five years. For that reason we focused on to determine the effects of urban transportation on air quality in the city center of Zonguldak/Turkey. The main objective of the study was to determine pollutant emissions in different parts of a highway and present it on emission maps. In this context, hourly vehicle counts were conducted at Zonguldak D010 highway in four zones in the coastal area. In addition, speed counts were carried out in the same zones. Emissions were calculated by the obtained data and IPCC guidance was used for these calculations. The IPCC guidelines include main headings such as energy, industrial processes, agriculture and waste. In this study, emission related data under the head of “energy” were used. Emission intensity maps for Zonguldak province were established by using the obtained values. The results of the study show that fuel consumption was the highest between 08:00 and 09:00 a.m. It decreases between 12:00 and 13:00 at noon and then tends to increase again between 18:00 and 19:00 p.m. Pollutant emissions were also higher in the morning and evening hours, depending on fuel consumption. In this study only the main arterial road was selected as study area. In future studies, by choosing whole road segments, the study area can be expanded and more accurate and reliable results can be obtained.